Predictive Role of Immune Profiling for Survival of Multiple Myeloma Patients - Zhaoyun, Liu; Rong, Fu (Frontiers in Immunology, 2021)
Multiple myeloma(MM) is still an uncurable disease. However, with rapidly increasing treatment options for MM patients, accompanied by the chance to achieve very deep responses or even reach MRD negativity. This lead the survival outcomes for patients have significantly improved. How to make a comprehensive evaluation to the prognosis of MM patients? All the standard now used such as IPSS,R-IPSS are related to myeloma cell characteristics. Myriad study have reveal that immune related the proliferation of myeloma cell and involved the evolution of disease. What is the role of immune situation to predict MM prognosis? Up to now, most of the reviews about immune profiling of myeloma focus on the immunotherapy and immune role in the bone marrow microenvironment. Little reviews reported the value of immune profiling on prognosis for myeloma patients. Especially in clinical work, Which immune index can predict the survival of myeloma patients is urgent to know. This review summarize immune index to predict prognostic significance to MM patients.